A method for treating and regenerating waste liquid after vanadium-titanium liquid flow battery circulation
Through the pretreatment and separation and purification of waste liquid after the vanadium-titanium liquid flow battery circulation, the reuse of vanadium and titanium is achieved, solving the problem of recycling high-value substances in battery waste liquid, reducing costs and improving environmental friendliness.
Patent Information
- Application Number
- CN202411216035.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-02
AI Technical Summary
After the vanadium titanium flow battery, high-value substances such as vanadium and titanium in the waste liquid cannot be effectively recycled, resulting in economic losses and environmental pollution.
Through pretreatment, preliminary separation, separation and purification of liquid phase and solid phase components, vanadium ion solution and titanium compound solution were obtained respectively, and the positive and negative electrode electrolytes of vanadium titanium liquid flow battery were re-prepared to realize the recycling of vanadium and titanium.
It significantly reduces the cost of the electrolyte, improves environmental friendliness, and uses the recovered titanium as the electrode material for sodium/potassium ion batteries. It has great economic value, and the process flow is simple, low cost and pollution-free.
Smart Images

Figure CN118763242B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste liquid treatment and recovery, and in particular relates to a method for treating and regenerating waste liquid after circulation of a vanadium-titanium liquid flow battery. Background Art
[0002] In energy storage technology, flow batteries have attracted much attention due to their unique characteristics of independent power and capacity, long life, safety and reliability, and flexible scale settings. The electrolyte of a flow battery consists of dissolved active molecules and corresponding supporting electrolytes, which are stored in the positive and negative electrode storage tanks respectively, and circulated between the positive and negative electrodes and the storage tanks by pumps. Among them, vanadium-titanium flow batteries have become a strong competitor for large-scale energy storage technology due to their advantages such as low cost and high performance. However, during the circulation process, cross-contamination will occur in the positive and negative electrolytes, resulting in a decrease in their capacity and efficiency, and finally leading to battery failure. At present, for the recycled solution, it is impossible to reuse high-value substances such as vanadium and titanium at the same time, resulting in economic losses. At the same time, traditional waste liquid treatment methods produce a large amount of chemical wastewater, which will pollute the environment.
[0003] In summary, how to efficiently separate and recycle the waste liquid after the vanadium-titanium flow battery cycle has become an urgent problem to be solved in this technology. Summary of the invention
[0004] The purpose of the present invention is to provide a method for treating and regenerating waste liquid after circulation of vanadium-titanium liquid flow batteries. The recovered vanadium and titanium components can be recycled as the electrolyte of the vanadium-titanium liquid flow battery, which can significantly reduce the cost of the electrolyte. At the same time, the recovered titanium component can be used as an electrode material for sodium and potassium ion batteries after processing, which has great economic application value and reduces pollution to the environment.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for treating and regenerating waste liquid after vanadium-titanium liquid flow battery circulation, comprising the following steps:
[0006] Step S1, pretreatment of waste liquid after vanadium-titanium liquid flow battery circulation;
[0007] Step S2, preliminarily separating the pretreated waste liquid to obtain a vanadium-containing liquid component and a titanium-containing solid component;
[0008] Step S3, separating and purifying the vanadium-containing liquid phase component to obtain a vanadium ion solution; separating and purifying the titanium-containing solid phase component and acid-treating it to obtain a solution containing a titanium compound;
[0009] Step S4, using the vanadium ion solution obtained in step S3 to prepare a positive electrode electrolyte for a vanadium-titanium liquid flow battery; using the titanium compound-containing solution obtained in step S3 to prepare a negative electrode electrolyte for a vanadium-titanium liquid flow battery;
[0010] The step S1 is specifically as follows:
[0011] The vanadium-titanium liquid flow battery electrolyte after circulation is collected in a liquid storage bottle and mechanically stirred, and then the solid impurities in the waste liquid after mechanical stirring are filtered out; the filtered electrolyte is electrochemically treated to convert the vanadium ions in the waste liquid into tetravalent ions by an electrochemical method; after the discharge is completed, the pretreated waste liquid is taken out from the positive electrode storage tank.
[0012] Furthermore, the step S2 is specifically as follows:
[0013] The pretreated waste liquid is added to a reaction container for heating treatment, a separation agent is slowly added to adjust the pH value of the waste liquid, and mechanical stirring is performed; the solution is cooled, the solution is ultrasonically treated, and after the solid in the waste liquid is completely precipitated, it is allowed to stand for a period of time; the solution is filtered using a filter and a separation operation is performed to separate the solid and liquid of the treated waste liquid, and a vanadium-containing liquid phase component and a titanium-containing solid phase component are obtained respectively.
[0014] Furthermore, the specific method for separating and purifying the vanadium-containing liquid phase component in step S3 is:
[0015] The liquid phase component preliminarily separated in step S2 is placed in an extraction bottle, and an extractant is added; after the solution and the extractant are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the mixture is allowed to stand for separation, and the organic layer liquid is taken out; the organic layer liquid and the stripping agent are added to the extraction bottle, and after the solution and the stripping agent are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the mixture is allowed to stand for separation, and the aqueous phase layer solution is taken out; the aqueous phase layer solution is placed in a reactor and heated to evaporate and concentrate the vanadium ion concentration in the solution to obtain a vanadium ion solution.
[0016] Furthermore, the specific method for separating, purifying and acid-treating the titanium-containing solid phase component in step S3 is:
[0017] The titanium-containing solid phase component is placed in a beaker, and deionized water is added and stirred thoroughly; after being fully mixed, an acid solution is added dropwise, and the solution pH is adjusted; the solution is ultrasonically treated, and the mixed solution is allowed to stand after the solid and the solution in the mixed solution are completely reacted; the mixed solution is filtered and separated to separate the solid and the liquid, and the precipitate is taken out, and it is washed with deionized water and dried to obtain a solid phase component containing the titanium compound;
[0018] The solid phase component of the titanium compound is added back into the acid solution and heated, and the solution is continuously mechanically stirred using a stirrer. After the solid is completely dissolved in the solution, the heating and stirring are stopped, and the solution is cooled to obtain a solution containing the titanium compound.
[0019] Furthermore, the step S4 is specifically as follows:
[0020] adding the vanadium ion solution obtained after separation and purification to an auxiliary acid solution to adjust the concentration, thereby obtaining a vanadium-titanium liquid flow positive electrode vanadium electrolyte;
[0021] Deionized water and an auxiliary acid solution are added to the titanium compound solution obtained after separation and purification to adjust the solution concentration, thereby obtaining a negative electrode titanium electrolyte for a vanadium-titanium liquid flow battery.
[0022] Furthermore, the separating agent in step S2 includes one or more of potassium hydroxide solution, sodium hydroxide solution, and ammonia solution; and the concentration of hydroxide ions in the separating agent is 2 mol / L to 12 mol / L.
[0023] Furthermore, in step S3:
[0024] The extractant includes one or more of di(2-ethylhexyl) phosphate and 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester;
[0025] The stripping agent includes one or more of sulfuric acid and hydrochloric acid, and the hydrogen ion concentration is 2mol / L~12mol / L;
[0026] The vanadium ion concentration in the vanadium ion solution is evaporated and concentrated to 0.5 mol / L~1.5 mol / L.
[0027] Furthermore, in step S3:
[0028] The acid solution is one of dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid;
[0029] The hydrogen ion concentration in the acid solution added for the first time is 2mol / L~6mol / L, and the hydrogen ion concentration in the acid solution added for the second time is 6mol / L~12mol / L.
[0030] Furthermore, in step S4:
[0031] The concentration of the vanadium compound solution is 0.5 mol / L~1.5 mol / L, the concentration of the titanium compound is 0.5 mol / L~1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L~12 mol / L.
[0032] The beneficial effects of the present invention are:
[0033] (1) The present invention can separate and recycle the waste liquid after the vanadium-titanium liquid flow battery is circulated, separate the vanadium compound and the titanium compound, and can respectively recycle the positive and negative electrode active substances mixed in the waste liquid, thereby realizing the reuse of the waste liquid and solving the problem that the positive and negative electrode electrolytes of the vanadium-titanium liquid flow battery cannot be used due to cross contamination after circulation, thereby significantly reducing the cost of the vanadium-titanium battery and improving its environmental friendliness. In addition, the solid phase titanium obtained after treatment can also be used as an electrode material for sodium / potassium ion batteries, which has great economic value.
[0034] (2) The separation agent required for separation in the present invention is low in cost, the extractant can be reused, and the process flow is simple and easy to operate. The overall recovery cost is low, and it is pollution-free and environmentally friendly, which is conducive to promoting industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 1 of the present invention.
[0037] Figure 2 This is a graph showing the relationship between the coulombic efficiency, voltage efficiency and energy efficiency and the number of cycles in the cycle test of the battery assembled in Example 1 of the present invention.
[0038] Figure 3 This is a Raman spectrum characterization result diagram of the solid phase titanium compound obtained in Example 2 of the present invention.
[0039] Figure 4 The x-ray photoelectron spectroscopy characterization results of the solid phase titanium compound obtained in Example 2 of the present invention, wherein (a) is the full x-ray photoelectron spectroscopy, (b) is the Ti2p peak and fitting results, (c) is the O1s peak and fitting results, and (d) is the K2p peak and fitting results.
[0040] Figure 5 This is a graph showing the relationship between specific capacity and number of cycles in the charge and discharge test of the potassium ion battery assembled in Example 3 of the present invention.
[0041] Figure 6 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 4 of the present invention.
[0042] Figure 7 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 5 of the present invention.
[0043] Figure 8 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 6 of the present invention.
[0044] Fig. 9 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 7 of the present invention.
[0045] Fig.10 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 8 of the present invention.
[0046] Fig.11 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 9 of the present invention.
[0047] Fig.12 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 10 of the present invention.
[0048] Fig.13 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 11 of the present invention.
[0049] Fig.14 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 14 of the present invention.
[0050] Fig.15 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 16 of the present invention.
[0051] Fig.16 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 17 of the present invention.
[0052] Fig.17 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 18 of the present invention.
[0053] Fig.18 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 19 of the present invention.
[0054] Fig.19 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 21 of the present invention.
[0055] Fig. 20 This is a capacity-voltage relationship diagram in the charge and discharge capacity test of the battery assembled in Example 22 of the present invention. DETAILED DESCRIPTION
[0056] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The present invention provides a method for treating and regenerating waste liquid after a vanadium-titanium liquid flow battery cycle, comprising the following steps:
[0058] (1) Wastewater pretreatment steps:
[0059] The vanadium-titanium liquid flow battery electrolyte after circulation is collected in a liquid storage bottle and mechanically stirred for 3 to 9 hours. A filter is used as a filtering device to screen out the solid impurities in the waste liquid after mechanical stirring. The filtered electrolyte is electrochemically treated and placed in the positive electrode storage tank of the cleaned liquid flow battery. The unused negative electrode (III) valence titanium electrolyte of the vanadium-titanium liquid flow battery is placed in the negative electrode storage tank to form a liquid flow battery and discharge the liquid flow battery at a constant current and constant voltage. The vanadium ions in the waste liquid are converted to (IV) valence by an electrochemical method, and the constant current discharge current density is 50mA / cm 2 ~500mA / cm 2 The cut-off voltage of the single cell constant current discharge is 0.45V~0.65V, and the cut-off current of the constant voltage discharge is 5mA / cm 2 -15mA / cm 2 During the discharge process, the specific parameter settings of the discharge current density, the cut-off voltage and the cut-off current are particularly important. For example, if the discharge cut-off voltage is too low, vanadium ions with a lower valence state are likely to appear; and if the discharge cut-off voltage is too high, vanadium ions with a higher valence state will appear. Regardless of whether the vanadium ions are in a higher or lower valence state, they will affect the subsequent solid-liquid separation step, produce vanadium precipitation to form vanadium impurities, and affect the separation of titanium ions. After the discharge is completed, the pretreated waste liquid is taken out from the positive electrode storage tank. The present invention converts all the vanadium ions in the waste liquid into tetravalent ions through an electrochemical method, so as to facilitate the subsequent steps to simultaneously separate vanadium and titanium ions. In the prior art, the vanadium ions of low-valent titanium are usually oxidized to the highest valence state (pentavalent) vanadium ions, and then the vanadium ions are separated. If the present invention converts the vanadium ions in the waste liquid into pentavalent vanadium ions, they will be converted into precipitates doped in the solid phase components containing titanium ions in the subsequent steps.
[0060] (2) Preliminary separation steps of waste liquid components:
[0061] Add the pretreated waste liquid to a high temperature resistant reaction container for heating treatment, and keep the solution temperature at 50℃~80℃. Slowly add a separating agent to adjust the pH value of the waste liquid to 2-12. The main components of the separating agent include one or more of potassium hydroxide solution, sodium hydroxide solution, and ammonia solution. The concentration of hydroxide ions in the separating agent is 2mol / L~12mol / L. Mechanical stirring is performed for 20min~60min. Cool the solution, keep the solution temperature at 10℃~30℃, ultrasonically treat the solution for 20min~60min, and after the solid in the waste liquid is completely precipitated, let it stand for 40min~60min. Use a filter to filter the solution and perform separation operations such as centrifugation to separate the solid and liquid of the treated waste liquid, and obtain a vanadium-containing liquid phase component and a titanium-containing solid phase component respectively. In the prior art, there are few records of separating vanadium and titanium ions simultaneously. The present invention adds a separation agent to provide hydroxide ions to change the pH of the vanadium and titanium ion solution, which can be adjusted to neutral, acidic or alkaline, and according to specific parameters, the titanium ions are precipitated in solid form.
[0062] (3) Liquid phase component separation and purification steps:
[0063] The liquid phase component of the waste liquid preliminarily separated in step (2) is placed in an extraction bottle, and an extractant is added, wherein the extractant includes one or more of di(2-ethylhexyl) phosphate and 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester. After the solution and the extractant are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the separation is allowed to stand, and the organic layer liquid is taken out; the organic layer liquid and the stripping agent are added to the extraction bottle, wherein the stripping aqueous solution includes one or more of sulfuric acid and hydrochloric acid, and the hydrogen ion concentration thereof is 2mol / L~12mol / L. After the solution and the stripping agent are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the separation is allowed to stand, and the aqueous phase layer solution is taken out. The solution is placed in a reactor and heated, and the solution temperature is controlled to be 60℃~90℃, and the vanadium ion concentration in the solution is evaporated and concentrated to 0.5mol / L~1.5mol / L. The obtained vanadium ion solution can be reused as a positive electrode electrolyte after concentration adjustment.
[0064] (4) Solid phase component separation and purification steps:
[0065] The solid phase components preliminarily separated from the waste liquid are placed in a beaker, and deionized water is added and stirred thoroughly. After being fully mixed, an acid solution is added dropwise, specifically one of dilute sulfuric acid / dilute hydrochloric acid / dilute nitric acid, wherein the hydrogen ion concentration is 2mol / L~6mol / L, and the solution is fully stirred at the same time. The addition is stopped after the solution pH is adjusted to 2~6; if the solution pH is too low, the subsequent titanium ions will not be completely precipitated, and if the solution pH is too high, there will be excess impurities and titanium ions precipitated at the same time; the solution is ultrasonically treated for 20min~60min, and after the solid in the mixed solution reacts completely with the solution, it is allowed to stand for 30min~60min. The mixed solution is filtered and centrifuged to separate the solid and liquid, the precipitate is taken out, washed with deionized water 3~5 times and dried to obtain the solid phase component containing the titanium compound.
[0066] The obtained solid phase component is added back into an acid solution with a hydrogen ion concentration of 6 mol / L to 12 mol / L, and the solution is placed in an induction cooker for heating, and the solution temperature is maintained at 50°C to 80°C. At the same time, the solution is continuously mechanically stirred with a stirrer for 2 to 6 hours. After the solid is completely dissolved in the solution, the solution is cooled to obtain a solution containing a titanium compound. The solution containing a titanium compound can be reused as a negative electrode electrolyte after concentration adjustment.
[0067] In addition, the obtained titanium compound solution is placed in an ice water bath, and potassium hydroxide / sodium hydroxide solution is quickly added thereto, wherein the hydroxide ion concentration is 6 mol / L~12 mol / L, and a glass rod is used to stir continuously, and the solution pH is measured at the same time, until the solution pH>14, the potassium hydroxide / sodium hydroxide solution is stopped from being added, wherein the potassium hydroxide / sodium hydroxide solution is added for no more than 30 minutes, and stirring is continued until the generated precipitate is completely precipitated. The solution and the precipitate are separated by centrifugation / filtration, and the precipitate is washed with deionized water several times until a solid phase titanium compound is obtained. After treatment, the solid phase titanium compound can be prepared as a positive electrode material for sodium / potassium ion batteries.
[0068] (5) Re-preparation of vanadium-titanium liquid flow battery electrolyte from separated components:
[0069] The vanadium-containing solution obtained after separation and purification in step (3) is added to an auxiliary acid solution, including sulfuric acid or hydrochloric acid; wherein the concentration of the vanadium compound solution is 0.5 mol / L~1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L~12 mol / L, and the concentration is determined according to the concentration of the vanadium compound, to obtain a vanadium-titanium liquid flow positive electrode vanadium electrolyte.
[0070] The titanium compound solution obtained after separation and purification in step (4) is added with deionized water and sulfuric acid or hydrochloric acid to adjust the concentrations of titanium and hydrogen ions in the solution to obtain a titanium electrolyte for the negative electrode of a vanadium-titanium liquid flow battery, wherein the concentration of the titanium compound is 0.5 mol / L to 1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L to 12 mol / L.
[0071] The vanadium electrolyte is added to the positive electrode storage tank of the vanadium-titanium liquid flow battery, and the titanium electrolyte is added to the negative electrode storage tank. The vanadium-titanium liquid flow battery using the vanadium and titanium electrolytes after separation, recovery and purification of the waste liquid is subjected to constant current charge and discharge tests on the battery test system to test its charge and discharge capacity and compare it with the vanadium-titanium liquid flow battery using the newly configured electrolyte, and the recovery rate of active substances in the waste liquid is calculated based on this. At the same time, its cycle performance and stability are tested.
[0072] (6) Characterization of solid phase titanium compounds and preparation as positive electrode materials for sodium / potassium ion batteries:
[0073] The solid phase titanium compound obtained in step (4) is characterized by Raman spectroscopy and X-ray photoelectron spectroscopy to determine its main components.
[0074] At the same time, the solid phase titanium compound obtained in step (4) is washed, dried, and ground into powder. The obtained titanium compound, carbon black, and PVDF are mixed in a ratio of 8:1:1, and NMP solution is added and stirred to obtain a slurry-like positive electrode material for an ion battery. The material is evenly coated on the surface of an aluminum foil, and the cut pieces are dried and weighed, and then assembled into button batteries (where the negative electrode materials, diaphragms, electrolytes, etc. used in the assembly process are all commercial materials) for constant current charge and discharge tests.
[0075] The design idea of the present invention is:
[0076] The vanadium ions in the waste liquid are charged / discharged to (IV) valence by an electrochemical method, and then the different solubilities of (IV) vanadium ions and (IV) titanium ions in weakly acidic / neutral aqueous solutions and at high / low temperatures are utilized. By adding an alkaline separation agent, changing the pH of the solution, and changing the dissolution and precipitation temperatures, the (IV) titanium ions are precipitated from the waste liquid in the form of solid precipitates, while the vanadium ions remain in the solution.
[0077] By utilizing the difference in solubility of (IV) vanadium ions in the neutral aqueous phase and the solubility of the extractant in the organic phase, the vanadium ions are transferred to the organic layer by extraction, and then back-extracted with an acid solution to back-extract the (IV) vanadium ions from the organic phase into the acidic aqueous phase solution, thereby removing impurities in the liquid phase components and obtaining a purified (IV) vanadium ion acid solution. The solution after adjusting the vanadium concentration and the acid concentration can be reused as a positive electrode electrolyte.
[0078] Taking advantage of the different solubility of (IV) valent titanium ions and vanadium ions under weakly acidic conditions, the pH is adjusted to wash away impurities such as vanadium ions in the solid phase component, and then based on the solubility curve of the titanium compound, an acid solution is added at high temperature to dissolve it to obtain a titanium compound solution. The solution can be reused as a negative electrode electrolyte by adjusting the titanium concentration and acid concentration.
[0079] Furthermore, by rapidly adding a titanium compound solution into an alkaline solution at low temperature, the corresponding cationic titanate can be precipitated, which can be reused as a positive electrode material for sodium / potassium ion batteries after simple treatment.
[0080] Example 1
[0081] The technical process for separating and recovering waste liquid after the vanadium-titanium liquid flow battery cycle in this embodiment includes the following steps:
[0082] (1) Wastewater pretreatment steps
[0083] The waste liquid after the vanadium-titanium liquid flow battery cycle was placed in a liquid storage bottle, mechanically stirred for 6 hours, and filtered using a filter. The filtered waste liquid was placed in the positive electrode storage tank of the cleaned liquid flow battery, and the original vanadium-titanium liquid flow battery negative electrode (III) valent titanium electrolyte was placed in the negative electrode storage tank, and the liquid flow battery was discharged at a constant current and constant voltage, and the constant current discharge current density was 300mA / cm 2 The cut-off voltage of the single cell constant current discharge is 0.5V, and the cut-off current of the constant voltage discharge is 10mA / cm 2 After the discharge is completed, the pretreated waste liquid is taken out from the positive electrode storage tank.
[0084] (2) Preliminary separation steps of waste liquid components
[0085] Add the pretreated waste liquid to a high temperature resistant reaction vessel, heat it, and keep the solution temperature at 65°C. Slowly add a separating agent, adjust the pH value of the waste liquid to 7, the main component of the separating agent is an ammonia solution, and the concentration of hydroxide ions in the solution is 6 mol / L. Mechanically stir for 40 minutes. Cool the solution, keep the solution temperature at 20°C, ultrasonically treat the solution for 40 minutes, and let it stand for 50 minutes after the solid in the waste liquid is completely precipitated. Use a filter to filter the solution and perform separation operations such as centrifugation to separate the solid and liquid of the treated waste liquid, and obtain a vanadium-containing liquid phase component and a titanium-containing solid phase component, respectively.
[0086] (3) Liquid phase component separation and purification steps
[0087] The liquid phase component of the waste liquid preliminarily separated in step (2) is placed in an extraction bottle, and an extractant is added, wherein the extractant is di(2-ethylhexyl) phosphate. After the solution and the extractant are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the separation is allowed to stand, and the organic layer liquid is taken out; the organic layer liquid and the stripping agent are added to the extraction bottle, wherein the stripping aqueous solution is sulfuric acid, and its hydrogen ion concentration is 6 mol / L. After the solution and the stripping agent are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the separation is allowed to stand, and the aqueous phase solution is taken out. The solution is placed in a reactor and heated, and the solution temperature is controlled to 80°C, and the vanadium ion concentration in the solution is evaporated and concentrated to 1 mol / L.
[0088] (4) Solid phase component separation and purification steps
[0089] The solid phase component preliminarily separated from the waste liquid is placed in a beaker, deionized water is added and stirred thoroughly, and after being fully mixed, dilute sulfuric acid is added dropwise, and its hydrogen ion concentration is 4 mol / L, and the solution is fully stirred at the same time, and the pH of the solution is adjusted to 4, and the addition is stopped. The solution is ultrasonically treated for 40 minutes, and after the solid in the mixed solution and the solution are completely reacted, it is allowed to stand for 40 minutes. The mixed solution is filtered and centrifuged to separate the solid and liquid, and the precipitate is taken out, washed with deionized water 4 times and dried to obtain the solid phase component of the titanium compound.
[0090] The obtained solid phase component is added back into a dilute sulfuric acid solution with a hydrogen ion concentration of 9 mol / L, and the solution is placed in an induction cooker for heating. The solution temperature is maintained at 70°C, and the solution is continuously mechanically stirred with a stirrer. The stirring process lasts for 4 hours. After the solid is completely dissolved in the solution, the solution is cooled to obtain a solution of titanium compound.
[0091] (5) Post-separation component testing steps
[0092] The vanadium-containing solution obtained after separation and purification in step (3) is added to an auxiliary acid solution, including sulfuric acid or hydrochloric acid; wherein the concentration of the vanadium compound is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L, and the concentration is determined according to the concentration of the vanadium compound, and a vanadium-titanium liquid flow positive electrode vanadium electrolyte is obtained. The titanium-containing compound solution obtained after separation and purification in step (4) is added with deionized water and sulfuric acid solution to adjust the concentration of titanium and hydrogen ions, and a vanadium-titanium liquid flow battery negative electrode titanium electrolyte is obtained, wherein the concentration of the titanium compound is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L.
[0093] The vanadium electrolyte is added to the positive electrode storage tank of the vanadium-titanium liquid flow battery, and the titanium electrolyte is added to the negative electrode storage tank. The vanadium-titanium liquid flow battery using the vanadium and titanium electrolytes after waste liquid separation and purification is subjected to constant current charge and discharge tests on the battery test system to test its charge and discharge capacity, such as Figure 1 As shown, the discharge capacity is 347 mAh, and the vanadium-titanium liquid flow battery using the newly configured electrolyte (i.e. Figure 1 The recovery rate was 92.3%. The cycle performance and stability were also tested. Figure 2 As shown, it can run stably for 300 cycles, with the coulomb efficiency maintained at more than 99% and the energy efficiency maintained at more than 80%.
[0094] Example 2
[0095] The difference from Example 1 is:
[0096] After obtaining the titanium compound solution in (4), the obtained titanium compound solution is placed in an ice water bath, and potassium hydroxide / sodium hydroxide solution is quickly added thereto, wherein the hydroxide ion concentration is 9 mol / L, and a glass rod is used to continuously stir, while measuring the solution pH, until the solution pH>14, then stop adding potassium hydroxide / sodium hydroxide solution, wherein the potassium hydroxide / sodium hydroxide solution is added for 20 minutes, and continue stirring until the generated precipitate is completely precipitated. The solution and the precipitate are separated by centrifugation and filtration, and the precipitate is washed with deionized water for multiple times to obtain a solid phase titanium compound.
[0097] In (5), the solid phase titanium compound obtained in step (4) is characterized by Raman spectroscopy and X-ray photoelectron spectroscopy to determine its main components.
[0098] The rest are the same as in Example 1.
[0099] The Raman spectrum characterization results of the solid phase titanium compound obtained in this example are as follows Figure 3 As shown, the X-ray photoelectron spectroscopy characterization results are as follows Figure 4 As shown in (a) to (d) in the figure, the Raman spectrum shows characteristic peaks related to potassium titanate. At the same time, the XPS full spectrum characterization results confirm that only O, Ti and K elements exist in the solid phase titanium compound, without any other elements. Furthermore, the fitting analysis of high-resolution Ti2p, K2p and O1s spectra verifies that the chemical composition of the solid phase titanium compound is potassium titanate.
[0100] Example 3
[0101] The difference from Example 2 is:
[0102] Step (5) is changed to: the solid phase titanium compound obtained in step (4) is washed, dried, and ground into powder, and the obtained titanium compound, carbon black, and PVDF are mixed in a ratio of 8:1:1, and NMP solution is added, stirred and mixed to obtain a slurry-like positive electrode material for an ion battery. The material is evenly coated on the surface of an aluminum foil, and the cut pieces are dried and weighed, and then button batteries are assembled for constant current charge and discharge tests.
[0103] The rest is the same as Example 2.
[0104] The recovered solid phase titanium compound obtained in this embodiment is used to assemble a potassium ion battery, such as Figure 5 As shown, the potassium ion battery assembled using recycled titanium as the potassium ion positive electrode material maintained a coulombic efficiency of more than 99% during 100 cycles, and the discharge specific capacity reached 245 mAh / g.
[0105] Example 4
[0106] The difference from Example 1 is:
[0107] (1) The constant current discharge current density is 500mA / cm 2 , cut-off voltage is 0.65V, constant voltage cut-off current is 15mA / cm 2 .
[0108] The rest are the same as in Example 1.
[0109] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Figure 6 The test shows that its charge and discharge capacity is 338 mAh, and the recovery rate is 89.9%. Its cycle performance and stability are tested, and its cycle stability is good, the coulomb efficiency of the cycle remains above 99%, and the energy efficiency remains above 80%.
[0110] Example 5
[0111] The difference from Example 1 is:
[0112] (1) The constant current discharge current density is 50mA / cm 2 , cut-off voltage is 0.45V, constant voltage cut-off current is 5mA / cm 2 .
[0113] The rest are the same as in Example 1.
[0114] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Figure 7 As shown, the test shows that its charge and discharge capacity is 322mAh, and the recovery rate is 85.6%. Its cycle performance and stability are tested, and its cycle stability is good, the coulomb efficiency of the cycle is maintained at more than 99%, and the energy efficiency is maintained at more than 80%.
[0115] Example 6
[0116] The difference from Example 1 is that in (2), the solution temperature is maintained at 80°C after the heating treatment.
[0117] The rest are the same as in Example 1.
[0118] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Figure 8 As shown, the test showed that its charge and discharge capacity was 271 mAh, and the recovery rate was 72.1%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.8%, and the energy efficiency reached 77.6%.
[0119] Example 7
[0120] The difference from Example 1 is that in (2), the solution temperature is maintained at 50°C after the heating treatment.
[0121] The rest are the same as in Example 1.
[0122] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig. 9 As shown, the test showed that its charge and discharge capacity was 282 mAh, and the recovery rate was 75.0%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.8%, and the energy efficiency reached 77.3%.
[0123] Example 8
[0124] The difference from Example 1 is that in (2), a separating agent is slowly added, and the main component of the separating agent is sodium hydroxide.
[0125] The rest are the same as in Example 1.
[0126] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.10 As shown, the test showed that its charge and discharge capacity was 363 mAh, and the recovery rate was 96.5%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.8%, and the energy efficiency reached 79.1%.
[0127] Example 9
[0128] The difference from Example 1 is that in (2), a separating agent is slowly added, and the main component of the separating agent is potassium hydroxide.
[0129] The rest are the same as in Example 1.
[0130] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.11 As shown, the test showed that its charge and discharge capacity was 353 mAh, and the recovery rate was 93.9%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.8%, and the energy efficiency reached 79.0%.
[0131] Example 10
[0132] The difference from Example 1 is that in (2), a separating agent is slowly added, and the main component of the separating agent is sodium carbonate.
[0133] The rest are the same as in Example 1.
[0134] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.12 As shown, the test showed that its charge and discharge capacity was 259 mAh, and the recovery rate was 68.8%. Its cycle performance and stability were tested, and its cycle stability was good, the cycle coulomb efficiency reached 99.7%, and the energy efficiency reached 77.3%.
[0135] Embodiment 11
[0136] The difference from Example 1 is that in (2), a separating agent is slowly added, and the main component of the separating agent is sodium bicarbonate.
[0137] The rest are the same as in Example 1.
[0138] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.13 As shown, the test shows that its charge and discharge capacity is 265mAh, and the recovery rate is 70.5%. Its cycle performance and stability are tested, and its cycle stability is good, the cycle coulomb efficiency is 99.8%, and the energy efficiency is 77.6%.
[0139] Example 12
[0140] The difference from Example 1 is that in (2), the concentration of hydroxide ions in the separation agent solution is 2 mol / L.
[0141] The rest are the same as in Example 1.
[0142] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 244 mAh, and the recovery rate was 64.9%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.6%, and the energy efficiency reached 79.6%.
[0143] Example 13
[0144] The difference from Example 1 is that in (2), the concentration of hydroxide ions in the separating agent solution is 12 mol / L.
[0145] The rest are the same as in Example 1.
[0146] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 233 mAh, and the recovery rate was 62.0%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.4%, and the energy efficiency reached 76.3%.
[0147] Embodiment 14
[0148] The difference from Example 1 is that in (2), the solution is cooled and the solution temperature is maintained at 10°C.
[0149] The rest are the same as in Example 1.
[0150] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.14 As shown, the test showed that its charge and discharge capacity was 245 mAh, and the recovery rate was 65.0%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.7%, and the energy efficiency reached 76.7%.
[0151] Embodiment 15
[0152] The difference from Example 1 is that in (2), the solution is cooled and the solution temperature is maintained at 30°C.
[0153] The rest are the same as in Example 1.
[0154] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 256 mAh, and the recovery rate was 68.1%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.6%, and the energy efficiency reached 77.1%.
[0155] Example 16
[0156] The difference from Example 1 is that in (2), a separation agent is slowly added to adjust the pH value of the waste liquid to 2.
[0157] The rest are the same as in Example 1.
[0158] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.15 As shown, the test showed that its charge and discharge capacity was 298 mAh, and the recovery rate was 79.3%. Its cycle performance and stability were tested, and its cycle stability was good, the cycle coulomb efficiency reached 99.8%, and the energy efficiency reached 77.6%.
[0159] Embodiment 17
[0160] The difference from Example 1 is that in (2), a separation agent is slowly added to adjust the pH value of the waste liquid to 12.
[0161] The rest are the same as in Example 1.
[0162] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.16 As shown, the test showed that its charge and discharge capacity was 171 mAh, and the recovery rate was 45.5%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.8%, and the energy efficiency reached 75.9%.
[0163] When the pH value is 12, the solution is alkaline, and part of the vanadium precipitates as solid, resulting in the loss of some vanadium in the solution, but nearly half of the vanadium ions can still be recovered at this pH; but when the pH is greater than 12, excessive losses will occur, so the pH value in the present invention is set at 12 as the upper limit.
[0164] Embodiment 18
[0165] The difference from Example 1 is that in (3), an extractant is added, wherein the extractant is 2-ethylhexyl mono-2-ethylhexyl phosphate.
[0166] The rest are the same as in Example 1.
[0167] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.17 As shown, the test shows that its charge and discharge capacity is 333mAh, and the recovery rate is 88.6%. Its cycle performance and stability are tested, and its cycle stability is good, the cycle coulomb efficiency reaches 99.7%, and the energy efficiency reaches 78.5%.
[0168] Embodiment 19
[0169] The difference from Example 1 is that in (3), the organic layer liquid and the stripping agent are added to the extraction bottle, wherein the stripping aqueous solution is hydrochloric acid, and its hydrogen ion concentration is 6 mol / L.
[0170] The rest are the same as in Example 1.
[0171] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.18 The test results show that its charge and discharge capacity is 329 mAh and the recovery rate is 87.5%. Its cycle performance and stability are tested and its cycle stability is good. The coulombic efficiency of the cycle reaches 99.8% and the energy efficiency reaches 79.1%.
[0172] Embodiment 20
[0173] The difference from Example 1 is that in (3), the organic layer liquid and the stripping agent are added to the extraction bottle, wherein the stripping aqueous solution is sulfuric acid, and its hydrogen ion concentration is 2 mol / L.
[0174] The rest are the same as in Example 1.
[0175] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 289 mAh, and the recovery rate was 76.9%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.6%, and the energy efficiency reached 77.3%.
[0176] Embodiment 21
[0177] The difference from Example 1 is that in (3), the organic layer liquid and the stripping agent are added to the extraction bottle, wherein the stripping aqueous solution is sulfuric acid, and its hydrogen ion concentration is 12 mol / L.
[0178] The rest are the same as in Example 1.
[0179] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig.19 As shown, the test showed that its charge and discharge capacity was 314 mAh, and the recovery rate was 83.5%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.7%, and the energy efficiency reached 77.8%.
[0180] Embodiment 22
[0181] The difference from Example 1 is that in (3), the solution is placed in a reaction kettle and heated, and the solution temperature is controlled at 60°C.
[0182] The rest are the same as in Example 1.
[0183] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. Fig. 20 As shown, the test showed that its charge and discharge capacity was 302mAh, and the recovery rate was 80.3%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.6%, and the energy efficiency reached 79.1%.
[0184] Embodiment 23
[0185] The difference from Example 1 is that in (3), the solution is placed in a reaction kettle and heated, and the solution temperature is controlled at 90°C.
[0186] The rest are the same as in Example 1.
[0187] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 314 mAh, and the recovery rate was 83.5%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.7%, and the energy efficiency reached 79.4%.
[0188] Embodiment 24
[0189] The difference from Example 1 is that in (3), the solution is placed in a reaction kettle and heated, the solution temperature is controlled to be 80° C., and the vanadium ion concentration in the solution is evaporated and concentrated to 0.5 mol / L.
[0190] The rest are the same as in Example 1.
[0191] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 336 mAh, and the recovery rate was 89.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.7%, and the energy efficiency reached 78.7%.
[0192] Embodiment 25
[0193] The difference from Example 1 is that in (3), the solution is placed in a reaction kettle and heated, the solution temperature is controlled to be 80° C., and the vanadium ion concentration in the solution is evaporated and concentrated to 1.5 mol / L.
[0194] The rest are the same as in Example 1.
[0195] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 325 mAh, and the recovery rate was 86.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.8%, and the energy efficiency reached 79.6%.
[0196] Embodiment 26
[0197] The difference from Example 1 is that in (4), the solution is fully stirred and the pH value of the solution is adjusted to 2.
[0198] The rest are the same as in Example 1.
[0199] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 327 mAh, and the recovery rate was 86.9%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.1%, and the energy efficiency reached 75.4%.
[0200] Embodiment 27
[0201] The difference from Example 1 is that in (4), the solution is fully stirred and the pH value of the solution is adjusted to 6.
[0202] The rest are the same as in Example 1.
[0203] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 277 mAh, and the recovery rate was 73.7%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.4%, and the energy efficiency reached 77.4%.
[0204] Embodiment 28
[0205] The difference from Example 1 is that in (4), the solution is placed in an induction cooker for heating, and the solution temperature is maintained at 50°C.
[0206] The rest are the same as in Example 1.
[0207] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 325 mAh, and the recovery rate was 86.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.8%, and the energy efficiency reached 79.6%.
[0208] Embodiment 29
[0209] The difference from Example 1 is that in (4), the solution is placed in an induction cooker for heating, and the solution temperature is maintained at 80°C.
[0210] The rest are the same as in Example 1.
[0211] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 307 mAh, and the recovery rate was 81.6%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.3%, and the energy efficiency reached 78.5%.
[0212] Embodiment 30
[0213] The difference from Example 1 is that in (4), the obtained solid phase component is added back into a dilute sulfuric acid solution having a hydrogen ion concentration of 6 mol / L.
[0214] The rest are the same as in Example 1.
[0215] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 321 mAh, and the recovery rate was 85.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.5%, and the energy efficiency reached 78.6%.
[0216] Embodiment 31
[0217] The difference from Example 1 is that in (4), the obtained solid phase component is added back into a dilute sulfuric acid solution having a hydrogen ion concentration of 12 mol / L.
[0218] The rest are the same as in Example 1.
[0219] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 296 mAh, and the recovery rate was 78.7%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.4%, and the energy efficiency reached 77.3%.
[0220] Embodiment 32
[0221] The difference from Example 1 is that in (5), the concentration of the vanadium compound solution is 0.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L.
[0222] The rest are the same as in Example 1.
[0223] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 337 mAh, and the recovery rate was 89.6%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.3%, and the energy efficiency reached 79.1%.
[0224] Embodiment 33
[0225] The difference from Example 1 is that in (5), the concentration of the vanadium compound solution is 1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L.
[0226] The rest are the same as in Example 1.
[0227] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 321 mAh, and the recovery rate was 85.3%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.1%, and the energy efficiency reached 78.4%.
[0228] Embodiment 34
[0229] The difference from Example 1 is that in (5), the concentration of the vanadium compound solution is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L.
[0230] The rest are the same as in Example 1.
[0231] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 328 mAh, and the recovery rate was 87.2%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.2%, and the energy efficiency reached 76.4%.
[0232] Embodiment 35
[0233] The difference from Example 1 is that in (5), the concentration of the vanadium compound solution is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 12 mol / L.
[0234] The rest are the same as in Example 1.
[0235] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 325 mAh, and the recovery rate was 86.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.1%, and the energy efficiency reached 78.6%.
[0236] Embodiment 36
[0237] The difference from Example 1 is that in (5), the concentration of titanium compound in the negative electrode titanium electrolyte of the vanadium-titanium liquid flow battery is 0.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L.
[0238] The rest are the same as in Example 1.
[0239] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 331 mAh, and the recovery rate was 88.0%. Its cycle performance and stability were tested, and its cycle stability was good, the coulombic efficiency of the cycle reached 99.4%, and the energy efficiency reached 78.2%.
[0240] Embodiment 37
[0241] The difference from Example 1 is that in (5), the concentration of titanium compound in the negative electrode titanium electrolyte of the vanadium-titanium liquid flow battery is 1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 6 mol / L.
[0242] The rest are the same as in Example 1.
[0243] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 336 mAh, and the recovery rate was 89.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.7%, and the energy efficiency reached 79.1%.
[0244] Embodiment 38
[0245] The difference from Example 1 is that in (5), the concentration of titanium compound in the negative electrode titanium electrolyte of the vanadium-titanium liquid flow battery is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L.
[0246] The rest are the same as in Example 1.
[0247] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 329 mAh, and the recovery rate was 87.5%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.5%, and the energy efficiency reached 79.5%.
[0248] Embodiment 39
[0249] The difference from Example 1 is that in (5), the concentration of titanium compound in the negative electrode titanium electrolyte of the vanadium-titanium liquid flow battery is 1 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 12 mol / L.
[0250] The rest are the same as in Example 1.
[0251] The recycled waste liquid obtained in this embodiment was assembled into a vanadium-titanium liquid flow battery for testing. The test showed that its charge and discharge capacity was 340 mAh, and the recovery rate was 90.4%. Its cycle performance and stability were tested, and its cycle stability was good, the coulomb efficiency of the cycle reached 99.4%, and the energy efficiency reached 79.2%.
[0252] Comparative Example 1
[0253] The difference from Example 1 is that: in (1), the constant current discharge cut-off voltage is 0.3V.
[0254] The rest are the same as in Example 1.
[0255] The valence state of the vanadium ions in the pretreated electrolyte obtained in this comparative example is not entirely IV vanadium, and vanadium ions with lower valence appear therein. After adding the separation agent, the solid phase component is green in color with obvious vanadium precipitation, resulting in a low recovery rate of vanadium ions in the liquid phase component and vanadium impurities in the solid phase component.
[0256] Comparative Example 2
[0257] The difference from Example 1 is that: in (1), the constant current discharge cut-off voltage is 0.8V.
[0258] The rest are the same as in Example 1.
[0259] The valence state of the vanadium ions in the pretreated electrolyte obtained in this comparative example is not entirely IV vanadium, and higher valence vanadium ions appear therein. After adding the separation agent, the solid phase component is yellowish in color, with obvious vanadium precipitation, generating vanadium pentoxide with certain toxicity, which makes the vanadium recovery rate in the liquid phase component low, and the solid phase component contains vanadium impurities.
[0260] Comparative Example 3
[0261] The difference from Example 1 is that in (2), the solution temperature is maintained at 40°C after the heating treatment.
[0262] The rest are the same as in Example 1.
[0263] Since the temperature is too low, it is not conducive to the conversion of titanium into solid precipitation. Therefore, the quality of the solid phase titanium component obtained after the waste liquid is recovered in this comparative example is low. After being configured into a titanium electrolyte, the amount of titanium compound substance therein is low. The assembled vanadium-titanium liquid flow battery is tested, and its charge and discharge capacity is 158 mAh, the recovery yield is 42.2%, and the recovery efficiency is low.
[0264] Comparative Example 4
[0265] The difference from Example 1 is that in (2), the solution temperature is maintained at 90°C after the heating treatment.
[0266] The rest are the same as in Example 1.
[0267] Since the vanadium in the solution will be converted into a solid form and precipitated due to excessively high temperature, the amount of vanadium substance in the liquid vanadium electrolyte obtained after the waste liquid is recovered in this comparative example is relatively low. The assembled vanadium-titanium liquid flow battery was tested and its charge and discharge capacity was 138 mAh, the recovery yield was 36.7%, and the recovery efficiency was relatively low.
[0268] Comparative Example 5
[0269] The difference from Example 1 is that in (2), the concentration of hydroxide ions in the separating agent solution is 1 mol / L.
[0270] The rest are the same as in Example 1.
[0271] In the waste liquid recovery of this comparative example, the liquid phase component obtained after preliminary separation has a large volume, resulting in a low concentration of vanadium ions therein, which leads to the loss of some vanadium active substances in the subsequent steps. The amount of vanadium substance in the vanadium electrolyte finally obtained is low. The assembled vanadium-titanium liquid flow battery is tested to have a charge and discharge capacity of 193 mAh, a recovery yield of 51.3%, and a low recovery efficiency.
[0272] Comparative Example 6
[0273] The difference from Example 1 is that, except for (2), the concentration of hydroxide ions in the separating agent solution is 16 mol / L.
[0274] The rest are the same as in Example 1.
[0275] Since the concentration of hydroxide ions in the separating agent is too high, the addition of the separating agent will cause the local reaction pH to be too high, causing the vanadium to turn into a brown precipitate. Therefore, in the initial recovery process of the waste liquid recovery in this comparative example, a brown precipitate appears on the surface of the waste liquid after adding the separating agent, resulting in the loss of part of the vanadium active substance in the subsequent steps. The amount of vanadium substance in the vanadium electrolyte obtained at last is low. The test of the assembled vanadium-titanium liquid flow battery shows that its charge and discharge capacity is 112 mAh, the recovery yield is 29.8%, and the recovery efficiency is low.
[0276] Comparative Example 7
[0277] The difference from Example 1 is that in (2), the solution is cooled and the solution temperature is maintained at 0°C.
[0278] The rest are the same as in Example 1.
[0279] In the initial recovery process of the waste liquid in this comparative example, due to the low temperature, the hydrogen bonds between water molecules increase, the movement of water molecules becomes more difficult, and the liquid viscosity increases, resulting in a certain liquid loss in the solid-liquid separation process, thereby causing the loss of some vanadium active substances. The amount of vanadium substance in the vanadium electrolyte finally obtained is low, and the assembled vanadium-titanium liquid flow battery is tested to have a charge and discharge capacity of 179 mAh, a recovery yield of 47.6%, and a low recovery efficiency.
[0280] Comparative Example 8
[0281] The difference from Example 1 is that in (2), the solution is cooled and the solution temperature is maintained at 50°C.
[0282] The rest are the same as in Example 1.
[0283] Since excessively high temperature will cause some vanadium to precipitate, the amount of vanadium substance in the liquid vanadium electrolyte obtained after the waste liquid is recovered in this comparative example is relatively low. The assembled vanadium-titanium liquid flow battery is tested to have a charge and discharge capacity of 193 mAh, a recovery yield of 51.3%, and a low recovery efficiency.
[0284] Comparative Example 9
[0285] The difference from Example 1 is that in (2), a separation agent is slowly added to adjust the pH value of the waste liquid to 1.
[0286] The rest are the same as in Example 1.
[0287] The solid phase component obtained after the waste liquid in this comparative example has a small mass, and the amount of titanium substance in the titanium electrolyte obtained by subsequent configuration is low. The assembled vanadium-titanium liquid flow battery is tested to have a charge and discharge capacity of 177 mAh, a recovery yield of 47.1%, and a low recovery efficiency.
[0288] Comparative Example 10
[0289] The difference from Example 1 is that in (2), a separation agent is slowly added to adjust the pH value of the waste liquid to 14.
[0290] The rest are the same as in Example 1.
[0291] The solid phase component obtained after the waste liquid is recovered in this comparative example has a relatively large mass, and brown insoluble matter appears therein, which is a vanadium impurity. The amount of vanadium substance in the vanadium electrolyte obtained by subsequent configuration is low, and there are certain impurities in the solid phase titanium component.
[0292] Comparative Example 11
[0293] The difference from Example 1 is that in (4), after being fully mixed, the solution is not placed in an induction cooker for heating.
[0294] The rest are the same as in Example 1.
[0295] The impurities in the titanium compound solution obtained after the waste liquid recovery in this comparative example cannot be dissolved, and the titanium electrolyte prepared after filtration leads to low energy efficiency of the assembled battery.
[0296] Comparative Example 12
[0297] The difference from Example 1 is that in 4), after being fully mixed, an acid solution is added to adjust the pH of the solution to 1.
[0298] The rest are the same as in Example 1.
[0299] In this comparative example, a certain amount of titanium loss occurs in the titanium compound solution obtained after the waste liquid is recovered, resulting in a low titanium recovery rate.
[0300] Comparative Example 13
[0301] The difference from Example 1 is that in (4), after sufficient mixing, an acid solution is added to adjust the solution pH to 7.
[0302] The rest are the same as in Example 1.
[0303] In this comparative example, certain impurities appear in the titanium compound solution obtained after the waste liquid is recovered, and the prepared titanium electrolyte leads to low energy efficiency of the assembled battery.
[0304] The results of the examples of the present invention show that the method developed by the present invention for effectively separating and recycling the circulating waste liquid of vanadium-titanium liquid flow batteries and recycling it has a high recovery rate, simple steps and low cost, which significantly reduces the cost of the overall electrolyte of the vanadium-titanium liquid flow battery, improves the environmental friendliness of the project, and solves the problems existing in the prior art. In short, the recycling method developed by the present invention has the advantages of low cost and high recovery rate, and can effectively promote the commercial application and development of vanadium-titanium liquid flow batteries.
[0305] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0306] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for treating and regenerating waste liquid after vanadium-titanium liquid flow battery circulation, It is characterized in that The following steps are involved: Step S1, pretreatment of waste liquid after vanadium-titanium liquid flow battery circulation; Step S2, preliminarily separating the pretreated waste liquid to obtain a vanadium-containing liquid component and a titanium-containing solid component; Step S3, separating and purifying the vanadium-containing liquid phase components to obtain a vanadium ion solution; Separating and purifying the titanium-containing solid phase component and treating it with acid to obtain a solution containing a titanium compound; Step S4, using the vanadium ion solution obtained in step S3 to prepare a positive electrode electrolyte for a vanadium-titanium liquid flow battery; using the titanium compound-containing solution obtained in step S3 to prepare a negative electrode electrolyte for a vanadium-titanium liquid flow battery; The step S1 is specifically as follows: The vanadium-titanium liquid flow battery electrolyte after circulation is collected in a liquid storage bottle, mechanically stirred, and then the solid impurities in the waste liquid after mechanical stirring are filtered out; the filtered electrolyte is electrochemically treated to convert the vanadium ions in the waste liquid into tetravalent ions through an electrochemical method; after the discharge is completed, the pre-treated waste liquid is taken out from the positive electrode storage tank; The step S2 is specifically as follows: The pretreated waste liquid is added to a reaction container for heating treatment, a separation agent is slowly added to adjust the pH value of the waste liquid to 6-7, and mechanical stirring is performed; the solution is cooled, the solution is ultrasonically treated, and after the solid in the waste liquid is completely precipitated, it is allowed to stand for a period of time; the solution is filtered using a filter and a separation operation is performed to separate the solid and liquid of the treated waste liquid, and a vanadium-containing liquid phase component and a titanium-containing solid phase component are obtained respectively.
2. A method for treating and regenerating waste liquid after a vanadium-titanium liquid flow battery cycle according to claim 1, It is characterized in that The specific method for separating and purifying the vanadium-containing liquid phase components in step S3 is: The liquid phase component preliminarily separated in step S2 is placed in an extraction bottle, and an extractant is added; after the solution and the extractant are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the organic layer is allowed to stand for separation, and the organic layer liquid is taken out; the organic layer liquid and the stripping agent are added to the extraction bottle, and after the solution and the stripping agent are separated, the extraction bottle is repeatedly shaken to fully mix the water layer and the organic layer, and then the water layer solution is taken out; The aqueous phase layer solution is placed in a reaction kettle and heated to evaporate and concentrate the vanadium ion concentration in the solution to obtain a vanadium ion solution.
3. A method for treating and regenerating waste liquid after a vanadium-titanium liquid flow battery cycle according to claim 1, It is characterized in that The specific method for separating, purifying and acid-treating the titanium-containing solid phase components in step S3 is: The titanium-containing solid phase component is placed in a beaker, and deionized water is added and stirred thoroughly; after being fully mixed, an acid solution is added dropwise, and the solution pH is adjusted; the solution is ultrasonically treated, and the mixed solution is allowed to stand after the solid and the solution in the mixed solution are completely reacted; the mixed solution is filtered and separated to separate the solid and the liquid, and the precipitate is taken out, and it is washed with deionized water and dried to obtain a solid phase component containing the titanium compound; The solid phase component of the titanium compound is added back into the acid solution and heated, and the solution is continuously mechanically stirred using a stirrer. After the solid is completely dissolved in the solution, the heating and stirring are stopped, and the solution is cooled to obtain a solution containing the titanium compound.
4. A method for treating and regenerating waste liquid after a vanadium-titanium liquid flow battery cycle according to claim 1, It is characterized in that The step S4 is specifically as follows: adding the vanadium ion solution obtained after separation and purification to an auxiliary acid solution to adjust the concentration, thereby obtaining a vanadium-titanium liquid flow positive electrode vanadium electrolyte; Deionized water and an auxiliary acid solution are added to the titanium compound solution obtained after separation and purification to adjust the solution concentration, thereby obtaining a negative electrode titanium electrolyte for a vanadium-titanium liquid flow battery.
5. A method for treating and regenerating waste liquid after recycling of vanadium-titanium liquid flow battery according to claim 1, It is characterized in that The separating agent in step S2 includes one or more of potassium hydroxide solution, sodium hydroxide solution, and ammonia solution; the concentration of hydroxide ions in the separating agent is 2 mol / L to 12 mol / L.
6. A method for treating and regenerating waste liquid after recycling of vanadium-titanium liquid flow battery according to claim 2, It is characterized in that In step S3: The extractant includes one or more of di(2-ethylhexyl) phosphate and 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester; The stripping agent includes one or more of sulfuric acid and hydrochloric acid, and the hydrogen ion concentration is 2mol / L~12mol / L; The vanadium ion concentration in the vanadium ion solution is evaporated and concentrated to 0.5 mol / L~1.5 mol / L.
7. A method for treating and regenerating waste liquid after recycling of vanadium-titanium liquid flow battery according to claim 3, It is characterized in that In step S3: The acid solution is one of dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid; The hydrogen ion concentration in the acid solution added for the first time is 2mol / L~6mol / L, and the hydrogen ion concentration in the acid solution added for the second time is 6mol / L~12mol / L.
8. A method for treating and regenerating waste liquid after recycling of vanadium-titanium liquid flow battery according to claim 4, It is characterized in that In step S4: The concentration of the vanadium compound solution is 0.5 mol / L~1.5 mol / L, the concentration of the titanium compound is 0.5 mol / L~1.5 mol / L, and the concentration of hydrogen ions in the auxiliary acid solution is 2 mol / L~12 mol / L.
Citation Information
Patent Citations
Technology for purifying scandium, titanium and vanadium from acid solution step by step
CN106191447A
Vanadium-titanium electrolyte, preparation method thereof and flow battery formed by vanadium-titanium electrolyte
CN115799587A
